Hepatitis B Viral Infection with Nephrotic Syndrome Treated with Lamivudine - Banu, NA; Khatoon, S; Quadir, E; Rahman, MM; Khan, MA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 230-233 The abstract of this article is available on the PubMed website